The protective effects of dezocine on interleukin-1β-induced inflammation, oxidative stress and apoptosis of human nucleus pulposus cells and the possible mechanisms. Issue 1 (1st January 2022) - Zhu, Fang; Duan, Wei; Zhong, Chao; Ji, Bing; Liu, Xinjun
ABSTRACT: Intervertebral disc degeneration (IDD) is a natural problem linked to the inflammation. We aimed to investigate the role of dezocine (DEZ) in the development of IDD. Human nucleus pulposus cells (HNPCs) induced by interleukin (IL)-1β was used as a cellular model of IDD. After treatment with DEZ, HNPCs viability was evaluated with a CCK-8 assay. Then, the levels of inflammatory factors, including IL-6 and tumor necrosis factor-α (TNF-α), and oxidative stress-related markers, including reactive oxygen species (ROS), malondialdehyde (MDA) and reduced glutathione (GSH), were tested by RT-qPCR or kits. TUNEL staining was employed to detect cell apoptosis and Western blot was used to determine the expression of proteins related to inflammation, oxidative stress, apoptosis, endoplasmic reticulum stress (ERS) and MAPK signaling. Afterward, PMA, a MAPK signaling pathway agonist, was adopted for exploring the regulatory effects of DEZ on MAPK pathway. Results indicated that DEZ enhanced cell viability of HNPCs after IL-1β exposure. DEZ alleviated the inflammation and oxidative stress, evidenced by decreased levels of IL-6, TNF-α, ROS, MDA, p-NF-κB p65, NF-κB p65 in nucleus, cox-2 and increased levels of NF-κB p65 in cytoplasm, GSH, SOD1 and SOD2. Moreover, DEZ notably inhibited IL-1β-induced apoptosis of HNPCs. Furthermore, DEZ suppressed the levels of ERS-related proteins. The levels of related proteins in MAPK signaling including p-P38 and p-ERK1/2 were remarkably reduced after DEZ administration. By contrast, PMA crippled the impacts of DEZ on inflammation, oxidative stress and apoptosis of HNPCs induced by IL-1β. Collectively, DEZ ameliorates IL-1β-induced HNPCs injury via inhibiting MAPK signaling.